Pengaruh Risiko Kredit, Risiko Likuiditas Dan Risiko Operasional Terhadap Profitabilitas Bank BUMN Periode 2013-2020 - Putri, Novita Alifia; Pardede, Robert Pius (Jurnal Ilmiah Akuntansi Kesatuan, 2023)
Bank is an intitution that serves at financial intermediary between parties who have excess funds with the underfunded. The goal of a bank is to earn profit. Bank have various risk because it involves public funds, these risks will cause losses if it is not managed propely and it will affect the profits to be obtained by the bank. The purpose of this study is to test the effect of Credit Risk, Liquidity Risk and Operational Risk in BUMN Banks period 2013-2020. The type of data used is quantitative data. The data that obtained from company’s financial statements. The population of this study are 4 companies of BUMN banks. The analytical method used is multiple linear regression test for state-owned. The results of study indicate that partially Credit Risk has no significant effect on profitability, partially Liquidity Risk has no significant effect on Profitability. And partially Operational Risk has significant effect on Profitability. Simultaneously Credit Risk, Liquidity Risk and Operational Risk has significant effect on Profitability. Keywords: Credit Risk, Liquidity Risk, Operational Risk and Profitability